Pengaruh Daya Tarik Wisata, Kualitas Pelayanan, dan Harga terhadap Minat Berkunjung Kembali Wisatawan: Studi Kasus pada Cepogo Cheese Park di Boyolali - Yumrotul Kasanah; Luki Sri Anggorowati; Listyowati Puji Rahayu; Lio Bijumes (Pusat Riset dan Inovasi Nasional, 2026)
This investigation aimed to evaluate how tourist attractions, the standard of service, and cost influence visitors' inclination to return to Cepogo Cheese Park in Boyolali Regency. A quantitative approach utilizing a causal associative research design was employed. Data was gathered through questionnaires employing a Likert scale, administered to 110 individuals who had previously experienced Cepogo Cheese Park. The selection of participants followed Data collection utilized a non-probability approach, specifically purposive sampling. For the statistical evaluation, SPSS, version 25, was employed, with a focus on multiple linear regression analysis. The results revealed that, when considered independently, the appeal of the destination exhibited a positive but minimal influence on the intention to revisit, as indicated by a significance value of 0.206, which is greater than the predetermined threshold of 0.05. Likewise, the quality of service demonstrated a positive but statistically insignificant effect, likewise above the 0.05 threshold, with a significance value of 0.253. In contrast, price demonstrated a significant positive relationship with the intention to revisit, exhibiting a significance level below 0.05 (< 0.000). Simultaneously, tourist attractions, service quality, and price significantly impact tourists' intention to revisit. The results of this study indicate that price is the most crucial factor in motivating tourists to return to Cepogo Cheese Park, surpassing the importance of tourist attractions and service quality.